Recurrent and weakly recurrent points in βG - Mostafa Nassar (International Journal of Mathematics and Mathematical Sciences)
It is shown in this paper that if βG is the Stone-Čech compactification of a group G, and G satisfying a certain condition, then there is a weakly recurrent point in βG which is not almost periodic, and if another condition will be added, then there is a recurrent point in βG which is not almost periodic point.